The Analysis Understanding of Mathematics Concepts as Seen from Students’ Self-Efficacy in Solving SPLDV - Intan Syalomi Hutabarat; Nizlel Huda; Roseli Theis (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to describe the level of student self-efficacy, analyze students’ ability to understand mathematical concepts in solving SPLDV problems in terms of high, medium, and low self- efficacy, and identify factors that influence differences in the ability to understand mathematical concepts. This study used a qualitative approach with a descriptive research type. The subjects were ninth-grade students at SMP Negeri 22, Jambi City, selected based on their self-efficacy levels. Data collection techniques included a self-efficacy questionnaire, a mathematical concept comprehension test, interviews, and think-aloud tests. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. Data validity was achieved through triangulation of techniques and sources.The results of the study showed that students with high self-efficacy were able to fulfill almost all indicators of mathematical concept understanding, namely restating concepts, classifying objects, presenting concepts in various forms of representation, and applying concepts in problem solving. Students with moderate self-efficacy were only able to fulfill some indicators of mathematical concept understanding, while students with low self-efficacy experienced difficulties in almost all indicators of concept understanding. Factors that influence differences in students’ mathematical concept understanding abilities include self-confidence levels, persistence in solving problems, previous learning experiences, and the ability to manage emotions when facing difficulties. This study is expected to be a consideration for teachers in designing mathematics learning that not only focuses on concept mastery, but also on strengthening students’ self-efficacy.